Apprenticeship Assistance - Thérien, Charles (Relations industrielles / Industrial Relations, 1952)
This article on the Act to assist apprenticeship and the enhancing of human capital has as its aim to remind the reader of some important ideas concerning this Act and its application in the Province of Quebec. The author recalls the principle at the basis of the Act, then emphasizes the moral and social aspect, examines its realizations within the profession itself, and views its future among the problems which it must meet. He concludes by insisting on the necessity of a very close cooperation between the various organizations trusted with the training of youth to form specialized labour.